Does E-Learning Trigger Epistemic Curiosity? - Seda SARAC; Enisa MEDE; Ergun AKGUN (Anı Publishing, 2022)
This study aimed to explore the perceptions of tertiary level students about e-learning and determine whether it triggers their epistemic curiosity. Semi-structured interviews were conducted with 78 undergraduate students enrolled in a foundation (non-profit, private) university in Turkey. Key thematic categories including the perceptions of motivation to seek new information in e-learning, desire to cope with challenging information in e-learning, desire to discover new, uncertain, and unpredictable information in learning, and barriers to e-learning were deduced. Digital and traditional tools emerged as motivating resources promoting curiosity in e-learning. E-learning experiences also fostered the curiosity to predict novel, risky, and uncertain information. Situational factors such as timing and workload were perceived as barriers to epistemic curiosity in e-learning. The gathered findings offered suggestions and pedagogical implications for triggering epistemic curiosity through e-learning in higher education.